Sepsis An Ongoing and Significant Challenge - Azevedo, Luciano (IntechOpen, 2012)
Sepsis is the major cause of death in non-cardiologic intensive care units around the world. Every year, billions of dollars are consumed in the treatment of sepsis and in research to understand its complex pathophysiology and therefore obtain future therapeutic opportunities. Despite the efforts of the scientists and medical practitioners, the mortality rates are still high and the incidence of sepsis is increasing. In this book we provide an update on several aspects of sepsis. Starting from the history of the disease and finishing with treatment of sepsis-associated organ dysfunctions, this book offers a wide scope of well-written and complete reviews concerning pathophysiological and therapeutic characteristics of sepsis. We hope that the work of the authors will provide a significant forum of discussion on the topic, and increase the awareness of the healthcare team regarding the important aspects of early recognition and treatment of this severe condition.